Analisis Peluang Investasi Dana Haji Pada Industri Halal Di Indonesia - Fathur Rahman; Marliyah Marliyah; Budi Dharma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Hajj Financial Investment is an activity that involves placing the financial resources of the Hajj Financial Management Agency in business activities that are not contrary to sharia principles and applicable laws and regulations. The purpose of this activity is to obtain returns after thinking about in-depth research on the risks and benefits that can be obtained from these business activities. The purpose of this study is to analyze opportunities for the use of Hajj funds in the halal industry sector. To collect data, this research uses a qualitative descriptive method consisting of conducting interviews and documenting the results. The results showed that investment of Hajj funds in the Halal industry has a lot of potential and opportunities are very large because the halal industry has many development opportunities. This is supported by Indonesia's Muslim population of 237.55 million. The halal industry is one of the best alternative investment instruments because it is productive and sustainable. Investment strategies in the halal industry can be carried out by collaborating with halal industry executors in Indonesia in the Halal Food, Halal Travel and Muslim Fashion sectors, which are leading sectors of the global industry. BPKH also faces various risks that cannot be separated from the management of Hajj finances, therefore risk management is one of the most fundamental aspects that need to be considered in the investment of Hajj funds by BPKH.